2014
DOI: 10.5902/1980509816614
|View full text |Cite
|
Sign up to set email alerts
|

ESTRUTURA E DISTRIBUIÇÃO ESPACIAL DE ANDIROBEIRAS (<i>Carapa</i> spp.) EM FLORESTA DE VÁRZEA DO ESTUÁRIO AMAZÔNICO

Abstract: RESUMOO objetivo geral deste trabalho foi avaliar se a densidade de ocorrência de andirobeiras é dependente da distância do rio Amazonas, analisando sua distribuição espacial e a estrutura diamétrica da população em um trecho de floretas de várzea no Estado do Amapá. Esse trabalho faz parte do projeto Florestam (Ecologia e manejo florestal para uso múltiplo de várzeas do estuário amazônico) e foi desenvolvido em uma área de proteção ambiental (APA) de 136,59 ha, localizada no Distrito da Fazendinha, município … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 1 publication
1
11
0
11
Order By: Relevance
“…However, in the area of this study, some individuals were registered close to the margins of the Mazagão channel, suggesting that they are more resistant to the energy of the current than individuals in the highland floodplain forests. Abreu et al (2014) also found an increase in population density of Carapa guianensis with increasing distance from the banks of the Amazon.…”
Section: Discussionmentioning
confidence: 67%
“…However, in the area of this study, some individuals were registered close to the margins of the Mazagão channel, suggesting that they are more resistant to the energy of the current than individuals in the highland floodplain forests. Abreu et al (2014) also found an increase in population density of Carapa guianensis with increasing distance from the banks of the Amazon.…”
Section: Discussionmentioning
confidence: 67%
“…Trata-se de uma planta arbórea perenifólia, heliófila, com ocorrência tanto em áreas de várzeas como de terra-firme, podendo atingir até 55 metros de altura, com fuste cilíndrico e reto de até 30 m (MELO et al, 2011). Os frutos possuem formato de cápsulas grande e grossa, do tipo indeiscentes (ABREU et al, 2014). Suas sementes apresentam coloração marrom, são grandes e recalcitrantes, podendo apresentar grande variação com relação a forma e tamanho (FERRAZ, 2003).…”
Section: Fundamentação Teóricaunclassified
“…Currently, the study of spatial distribution patterns of tree species is a widely used and a promising tool to understand the behavior of several species (Capretz et al, 2012;Loregian et al, 2012;Vieira et al, 2013;Abreu et al, 2014). Knowledge about patterns of spatial distribution of tree species can provide important information on the ecological processes and characteristics of the environment itself and assist in sampling processes regarding the studied species (Capretz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%